Transitioning to Better Jobs in the Kyrgyz Republic : A jobs Diagnostic - World Bank (Washington, DC, 2015)
This report takes an in-depth look at the development of jobs in the Kyrgyz Republic over the past decade to understand why the country has not realized better job outcomes. Drawing on evidence at the macro, household, and firm level, it examines key shortcomings in the current migration-led, remittance-driven development model that have weakened the country’s ability to create sufficient and high-quality employment opportunities and are likely to result in deteriorating job outcomes in the future. The report argues that several broad transformations will be needed to develop engines of growth in the Kyrgyz Republic outside remittances and shift to a better jobs path. The distortions and obstacles that currently prevent the expansion of private sector employment need to be unraveled; macroeconomic, regulatory, and logistical impediments to greater, more diversified export orientation need to be strategically addressed; the compensation of public employees must be reformed to reduce the level of corruption that discourages business growth; and the migration phenomenon, which will be a part of the employment mosaic for at least another decade, must be made to contribute to domestic employment creation and the country’s development.